Corn Consumer Behavior Study at PJR (Penjual Jagung Rebus) Konawe Regency: A Conjoint Analysis - Purbaningsih, Yuli; Helviani, Helviani; Juliatmaja, Aan Wilhan; Surahturohmi, Indriani Nurul (University of Jember, 2024)
Carrying out this study is important because the results of this study can be used as consideration by the local government, especially in determining the direction and policies related to the development of the PJR MSME Culinary Tourism Center and the development of Cornware. This research aims to find out how consumer behaviour influences the purchasing decision process, consumer preferences, and consumer satisfaction in purchasing cooked corn at PJR Pondidaha. This research was conducted using quantitative descriptive techniques using Engel model analysis tools, conjoint analysis, and consumer satisfaction index analysis. The sample was determined using the random sampling method because the population was homogeneous and the sample consisted of 100 respondents. Based on survey results, from consumer behaviour based on the purchasing decision process, the benefit sought when purchasing boiled corn is that the location of the boiled corn shop is very good, suitable for stopping by during breaks or when leaving the house. I found that I could enjoy cooked corn dishes. I'm tired and hungry. journey. The colour attribute (variety) of cooked corn is the most important and important consideration for consumers in buying something that suits their tastes. Consumer satisfaction is “satisfied'' and there is a tendency to prefer ripe corn which is white in colour (varies), tastes sweet and is cheap.